RELEVANSI QIYAS UANG KERTAS TERHADAP EMAS DAN PERAK - Barakah, Ainun (Jurnal Kajian Hukum Islam, 2019)
There is a debate between the scholars about the status of banknotes, whether he can be sent to Naqdain (gold and silver) or not, or can be given but not completely. If it can be based on gold and silver, What is the legal consequence? What law is accompanying it? Is there any similarity between paper money and silver gold so it can be in the state, how the scholars ' views and opinions on the law of banknotes. In this research, some of the questions above are described and shown in the following scholars in each group, accompanied by arguments from each party. Keywords : qiyas, naqdain. Emas dan Perak